Effect of Different Surface Treatments on the Micro-Shear Bond Strength and Surface Characteristics of Zirconia: An In Vitro Study - Ann Sales; Shobha J. Rodrigues; M. Mahesh; Kishore Ginjupalli; Thilak Shetty; Umesh Y. Pai; Sharon Saldanha; Puneeth Hegde; Sandipan Mukherjee; Vignesh Kamath; Prashant Bajantri; N. Srikant; et al. (Hindawi Limited, 2022)
Purpose. To study the effect of different surface treatments on the micro-shear bond strength and surface characteristics of zirconia. Methods. Two types of zirconia ceramics were tested: opaque (O) and translucent (T). Each type of zirconia was further allotted into four groups based on the type of surface treatment method. The four groups were: control (C), air abrasion with 110 µm Al2O3 particles (A), etching with Zircos-E Etching solution for 2 hours (E), and a combination of air abrasion and etching (AE). After the surface treatment, all specimens were ultrasonically cleaned and 10 resin cement cylinders were attached to the zirconia discs in each group. A micro-shear bond strength test was performed in a universal testing machine at a crosshead speed of 0.5 mm/min. The fracture surfaces were assessed under a compound microscope. SEM, EDAX, and AFM analyses were done for the zirconia specimens after being subjected to surface treatment. Statistical analysis for the bond strength test was done using the Shapiro-Wilk test, one-way analysis of variance (ANOVA), and Post hoc Tukey test. Results. The micro-shear bond strength values for the groups were as follows in megapascals (MPa): OC 18.96 (5.54), OA 22.66 (2.51), OE 28.48 (4.50), OAE 28.63 (4.53), TC 22.82 (5.46), TA 25.36 (5.17), TE 28.12 (4.76), and TAE 32.00 (3.47). The one-way analysis of variance (ANOVA) and post hoc Tukey HSD tests were done which showed significant results in the groups. In opaque zirconia, significant differences were seen in the etching and air abrasion with etching groups when compared with the control and air abrasion groups. There was no difference between the etching and air abrasion with etching groups. For translucent zirconia, the only significant difference was seen in the air abrasion with etching group in comparison with the control and air abrasion groups. The mode of failure was majorly adhesive. The surface topography and surface roughness showed significant differences between the groups. The EDAX results showed material loss that occurred due to sandblasting in the air abrasion groups. Conclusions. Etching with Zircos-E Etching solution significantly increased the bond strength of zirconia to resin cement when compared with other surface treatment methods. In translucent zirconia, the best results can be achieved by combining etching with air abrasion.